APAKAH TEORI FRAUD PENTAGON RELEVAN DALAM MENDETEKSI PENGGELAPAN PAJAK? - Ayu Fury Puspita; Devi Pusposari; Yuki Firmanto (Universitas Brawijaya, 2021)
Abstrak – Apakah Teori Fraud Pentagon Relevan dalam Mendeteksi Penggelapan Pajak?Tujuan Utama – Penelitian ini memiliki tujuan menguji adanya dampak efek variabel berdasarkan teori fraud pentagon sebagai deteksi indikasi penggelapan pajak.Metode – Uji t digunakan sebagai metode analisis. Adapun sampel penelitian adalah perusahaan industri dagang yang tercatat dalam Bursa Indonesia selama periode 2015 hingga 2019.Temuan Utama – Teori fraud pentagon tidak relevan dalam melakukan deteksi penggelapan pajak. Pengujian ini memberikan bukti empiris bahwa tidak terjadi indikasi penggelapan pajak dengan melakukan kecurangan akuntansi pada laporan finansial. Unsur tekanan yang diukur dengan 3 proksi tidak mengindikasi dapat terjadi penggelapan pajak.Implikasi Teori dan Kebijakan – Kenaikan atau penurunan rasio keuangan bukan menjadi indikator penggelapan pajak. Hal demikian juga berlaku pada susunan manajemen puncak dan CEO.Kebaharuan Penelitian - Penelitian ini menggabungkan Beneish dan Stuben Model berdasarkan teori fraud pentagon sebagai peringatan dini untuk mengindikasi penggelapan pajak. Abstract – Is the Pentagon's Fraud Theory Relevant in Detecting Tax Evasion? Main Purpose - This study aims to test the impact of variable effects based on the pentagon's fraud theory to indicate tax evasion. Method – The t-test is used as an analysis method. The research sample is a trading industry company listed on the Indonesia Exchange from 2015 to 2019. Main Findings - The Pentagon's fraud theory is irrelevant in detecting tax evasion. This test provides empirical evidence that there is no indication of tax evasion by committing accounting fraud on financial statements. As measured by three proxies, the pressure element does not indicate that tax evasion can occur. Theory and Practical Implications – The increase or decrease in the financial ratio is not an indicator of tax evasion. The same goes for top management and CEOs. Novelty – This study combines the Beneish and Stuben Models based on the pentagon's fraud theory as an early warning to indicate tax evasion.Abstract – Is the Pentagon's Fraud Theory Relevant in Detecting Tax Evasion? Main Purpose - This study aims to test the impact of variable effects based on the pentagon's fraud theory to indicate tax evasion. Method – The t-test is used as an analysis method. The research sample is a trading industry company listed on the Indonesia Exchange from 2015 to 2019. Main Findings - The Pentagon's fraud theory is irrelevant in detecting tax evasion. This test provides empirical evidence that there is no indication of tax evasion by committing accounting fraud on financial statements. As measured by three proxies, the pressure element does not indicate that tax evasion can occur. Theory and Practical Implications – The increase or decrease in the financial ratio is not an indicator of tax evasion. The same goes for top management and CEOs. Novelty – This study combines the Beneish and Stuben Models based on the pentagon's fraud theory as an early warning to indicate tax evasion.